Macchupicchu: perspectivas de espacio y tiempo - Bueno Mendoza, Alberto (2007)
Thc new archaeological studies allow lo have IIOW a conception differentfrom the ideas provided bv the history it brings OH:r ofMacchupicchu. The history tchronicles ofthe Xl/Ith and Xl/Ilth century) does not llave information brings over ofMacchupicchu. rile written information begins with the European travelers. being travelling French Charl es JViener (lR75- !8 7 7). who records the first infarmationfrom the surroundings ofthe archaeological city. In thefirst half of the 20t" century (/9/0-19/3) the North American explorer lliram Bingham reveals it to the world, managing TO write articles ami books in which it (he, she) exposes the ideas ofthe epoch, overcotne the present. The doctor ./01111 /1 ROlI"e. archeologist, anthropologist and North American historian. published in 1990 documentary information relating to which Macchupicchu ~msa seat ofpersoual domain (control) of the Inka Pachakuti. In litis work, one raises. from thc archaeological perspective. that the Sacred Vallev ami Macchupicchu llave two cultural periods: l} Culture Tampu: 2) Culture Cusco.